Eco-Efficiency and Financial Performance: Empirical Evidence of Companies in Indonesia - Inten Meutia; Shelly F Kartasar (Fakultas Ekonomi, Universitas Bangka Belitung, 2023)
This study aims to identify and analyze energy consumption and emissions produced by companies listed on the Indonesia Stock Exchange after the Circular Letter of The Financial Services Authority number 16 of 2021 regarding the obligation to prepare Sustainability Reports. In addition, this study tries to provide evidence regarding the relationship between eco-efficiency and company financial performance. The research population is all companies listed on the Indonesia Stock Exchange in 2021 and 2022. The research sample is a company that has prepared separate sustainability reports and has energy consumption and emission data for 134 companies. This study documents that energy efficiency and emissions significantly impact ROA in all sectors, including sensitive industries. This research supports the stakeholder theory in the context that companies responsible for balancing all stakeholders' interests can lead to long-term success and sustainability.